Vilões ou vítimas: ampliando a percepção dos alunos acerca dos ofídios por meio de sequência didática investigativa - Linhares, Luciana Fernandes (2024)
Snakes are animals with an elongated body, characterized by the presence of scales, the absence of legs and that move by crawling. These beings are classified as belonging to the Class Reptilia, Order Squamata and Suborder Serpents. Biology and Zoology are areas of study dedicated to understanding animal life in its various aspects, in the case of snakes, they are concerned with studying the anatomy, physiology, behavior and ecology of these animals. Ophidians are often labeled as dangerous and malignant beings, contributing to the existence of fear or aversion which, associated with people's lack of knowledge, has brought negative consequences for the conservation of these reptiles. With the intention of promoting teaching about snakes in Biology classes, from the perspective of teaching through investigation, this theme was chosen as support for the development of innovative strategies and production of active methodologies with a focus on meaningful learning and student protagonism. The study was developed at Escola Cidadã Integral Técnica Estadual Henrique Fernandes de Farias, part of the state public education network, located in the city of Curral de Cima/PB, with 31 students from the 2nd year of Technical High School. To develop this study, we opted for a qualitative-quantitative approach, focusing on participant observation, starting with a survey of students' previous conceptions through a survey questionnaire with the intention of verifying students' knowledge in relation to snakes. The data collected served as a basis for the elaboration of three investigative didactic sequences, used during a didactic intervention aimed at promoting students' learning about snakebites. The first sequence sought to recover the students' prior knowledge about snakes and promote the appropriation of basic concepts about these reptiles. The second consisted of the application of the active inverted classroom methodology, deepening the study of snakes through research, in addition to the application of the interactive game Myth or Truth about snakes, with the intention of deconstructing myths and prejudices about these animals. The third consisted of an interdisciplinary approach involving the Biology component and the disciplines Social and Scientific Innovation and Technological and Media Education from the IT technical course in the application of the maker culture methodology, in which students focused on research and preparation of informative materials about snakes. Three weeks after the intervention, a second questionnaire was administered with the purpose of evaluating the effectiveness of the approaches developed. It is assessed, based on observation and collected data, that student participation and involvement improved with the application of the strategies, which allowed for a new meaning and expansion of students' perceptions regarding the importance of snakes for the ecosystem and the public health. At the end of the execution, all the strategies produced were gathered into a teaching guide, intended for basic education teachers, as a resource to contribute to the teaching-learning process about snakebites.